An unusual case report on intracranial hydatid cyst with intraventricular extension - Rohan Kumar Singh; Prerna Anup Patwa; Gaurav Vedprakash Mishra; Rajasbala Pradeep Dhande; Shivali Vaibhav Kashikar; Bhavik Sunit Unadkat (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background We report an interesting case of a primary isolated intraventricular and intracranial hydatid cyst in 20-year-old female that mimicked bleeding cystic tumor presenting as intraventricular hemorrhage with hydrocephalus. Case presentation Patient presented with headache and giddiness for 1 month. On magnetic resonance imaging, there was multiloculated multi-cystic lesion in left lateral ventricle and adjacent left periventricular deep white matter. Lesion was causing compression of the body of the left lateral ventricle with temporal horn dilatation and midline shift of 17–18 mm toward right side. On investigation, it was diagnosed intracranial hydatid cyst with intraventricular extension. Patient underwent complete removal of cerebral hydatid cyst. Follow-up postoperative computed tomography scan done which revealed no residual hydatid cyst. Conclusion In this case, larvae of echinococcus might have passed through capillaries of liver and lungs and entered systemic circulation reaching brain. Intracerebral hydatid cysts are rare and hence, dangerous if the diagnosis and treatment is not prompt. Intracerebral hydatid cysts have slow growth rate with late-stage symptoms, morbidity and mortality are high. So, take home message is whenever intracranial cystic lesion are found on magnetic resonance imaging hydatid cyst with possible intracranial extension should be considered in differential diagnosis.